HOMEOPATHY IS UNSCIENTIFIC AND UNETHICAL - Smith, Kevin (Bioethics, 2012)
In opposition to the premises of Against Homeopathy – a Utilitarian Perspective, all four respondents base their objections on the central claims that homeopathy is in fact scientifically plausible and is supported by empirical evidence. Despite ethical aspects forming the main thrust of Against Homeopathy, the respondents’ focus on scientific aspects represents sound strategy, since the ethical case against homeopathy would be weakened concomitant with the extent to which any plausibility for homeopathy could be demonstrated. The trouble here is that the respondents are attempting to perpetuate a sterile debate. The notion that homeopathic preparations could have any biological effects represents a fringe viewpoint, one not entertained by serious scientists nor supported by reason and evidence. In the present article, I shall endeavour to explain why the respondents do not have a valid case. I will deal firstly with their general approach to scientific plausibility and evidence, and then consider some of the specific claims they have made. Finally, I will answer the philosophical arguments some of the respondents have raised.